Lysosomes: Regulators of autophagy in the retinal pigmented epithelium. (March 2016) - Sinha, Debasish; Valapala, Mallika; Shang, Peng; Hose, Stacey; Grebe, Rhonda; Lutty, Gerard A.; Zigler, J. Samuel; Kaarniranta, Kai; Handa, James T.
Abstract: The retinal pigmented epithelium (RPE) is critically important to retinal homeostasis, in part due to its very active processes of phagocytosis and autophagy. Both of these processes depend upon the normal functioning of lysosomes, organelles which must fuse with (auto)phagosomes to deliver the hydrolases that effect degradation of cargo. It has become clear that signaling through mTOR complex 1 (mTORC1), is very important in the regulation of lysosomal function. This signaling pathway is becoming a target for therapeutic intervention in diseases, including age-related macular degeneration (AMD), where lysosomal function is defective. In addition, our laboratory has been studying animal models in which the gene ( Cryba1 ) for βA3/A1-crystallin is deficient. These animals exhibit impaired lysosomal clearance in the RPE and pathological signs that are similar to some of those seen in AMD patients. The data demonstrate that βA3/A1-crystallin localizes to lysosomes in the RPE and that it is a binding partner of V-ATPase, the proton pump that acidifies the lysosomal lumen. This suggests that βA3/A1-crystallin may also be a potential target for therapeutic intervention in AMD. In this review, we focus on effector molecules that impact the lysosomal–autophagic pathway in RPE cells. Highlights: In the RPE, lysosomes modulate both heterophagy and autophagy to maintain retinal homeostasis. The mTORC1 signaling pathway regulates the biogenesis, distribution and activity of lysosomes. βA3/A1-crystallin is a novel target for restoring normal lysosome function in human AMD disease.